Neglected complete bilateral achilles tendon rupture. clinical case presentation, treatment and follow-up - Polidoro, Federico; Rea, Roberto; Fascione, Fabrizio; Salini, Vincenzo; Belluati, Alberto (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: subcutaneous Achilles tendon lesions are common degenerativetendon tears, often related to sport activities, multiple pharmacotherapies and internal medicalcomorbidities. Neglect an Achilles tendon lesion can affect walk ability, while neglect a bilateral lesioncould really lead to a serious limitation of self-sufficiency in daily living. We report a case of chronicbilateral Achilles tendon lesion successful treated with LARS augmentation, along with some clinicalconsiderations concerning the clinical outcome. Methods: we report a case of a chronic bilateral Achillestendon lesion in an elderly man with multiple comorbidities, successful treated with LARS reconstruction,along with some considerations concerning possible intraoperative issues and the clinical outcome. Results:good functional result was obtained as documented with pre and postoperative American Orthopedic FootAnd Ankle Society Scale and the “Foot And Ankle Disability Index”, without complications. Conclusions:a bilateral Achilles tendon rupture is a very disabling pathology, that needs prompt diagnosis and treatmentto prevent further complications. LARS reconstruction could be an effective method in selected patients toavoid some intraoperative issues related to patient comorbidities and ability to follow complex postoperativerehabilitation protocols. (www.actabiomedica.it)